Rare Somatic MEN1 Gene Pathogenic Variant in a Patient Affected by Atypical Parathyroid Adenoma - Luigia Cinque; Flavia Pugliese; Celeste Clemente; Stefano Castellana; Maria Pia Leone; Danilo de Martino; Teresa Balsamo; Claudia Battista; Tommaso Biagini; Paolo Graziano; Marco Castori; Alfredo Scillitani; et al. (International Journal of Endocrinology)
Objective. Atypical parathyroid adenoma is a rare neoplasm, showing atypical histological features intermediate between classic benign adenoma and the rarest parathyroid carcinoma, whose the clinical behaviour and outcome is not yet understood or predictable. Up to date only two cases of atypical adenoma were found associated to a MEN1 syndrome, and only one was proved to carry a pathogenic variant of the MEN1 gene. Design. We report the clinical, histologic, and molecular findings of a 44-year-old woman, presenting with a histologically proved atypical parathyroid adenoma with an apparent aggressive behaviour. Methods and Results. CDC73 gene was screened at germline and somatic levels with no results. Whole exome sequencing performed on DNA extracted from blood leukocytes and tumour tissue revealed a somatic MEN1 gene heterozygous variant, c.912+1G > A, of the splicing donor site of exon 6. On immunohistochemistry, downregulation of the menin protein expression in the neoplastic cells was also observed. Conclusions. We report the second case of a rare association of a somatic MEN1 gene mutation in a patient with atypical parathyroid adenoma. We suggest that MEN1 gene could be an underestimate genetic determinant of these rare histological entities, and we highlight the utility of a complete genetic screening protocol, by the use of next-generation sequencing technology in such undetermined clinical cases with no frank clinical presentation.